2017
DOI: 10.2741/4571
|View full text |Cite
|
Sign up to set email alerts
|

A review of computational approaches detecting microRNAs involved in cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs playing an essential role in gene expression regulation. Multiple studies have demonstrated that miRNAs are dysregulated in cancer initiation and progression, pointing out their potential as biomarkers for diagnosis, prognosis and response to treatment. With the introduction of high-throughput technologies several computational approaches have been proposed to identify cancer-associated miRNAs. Here, we present a systematic and comprehensive overview of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 102 publications
4
11
0
Order By: Relevance
“…16 Integrative computational bioinformatics approaches have been utilized as an effective tool to detect the potential outlier miRNAs in cancer. 20,21 Furthermore, as a rational approach, preliminary detection of candidate miRNAs derived from large-scale expression profiling data and low-throughput experimental verification for the selected outlier miRNAs can be used to choose candidate miRNAs. 22,23 In the present study, according to literature reviews and data mining for were culled to be analyzed and confirmed by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…16 Integrative computational bioinformatics approaches have been utilized as an effective tool to detect the potential outlier miRNAs in cancer. 20,21 Furthermore, as a rational approach, preliminary detection of candidate miRNAs derived from large-scale expression profiling data and low-throughput experimental verification for the selected outlier miRNAs can be used to choose candidate miRNAs. 22,23 In the present study, according to literature reviews and data mining for were culled to be analyzed and confirmed by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Since >30% of annotated human miRNAs are organized in genomic clusters, we can expect to find other oncogenic/tumor suppressor polycistronic miRNAs that are co-expressed to jointly regulate molecular pathways involved in cancer malignancy. Existing computational approaches for the identification of master miRNA regulators involved in cancer onset and subtyping are typically designed to detect the effect of a single miRNA (see review in (19)). However, miRNAs have been shown to frequently act in a combined manner, jointly regulating proteins in close proximity of the protein-protein interaction network (20) and functionally related genes (21–25).…”
Section: Introductionmentioning
confidence: 99%
“…In cancer as well as many other diseases, the involvement of miRs is becoming more and more evident with the help of the latest computational tools, which can reliably predict miR-disease associations to expedite experimental discoveries [80,81,82]. Besides ranking-based methods that focus primarily on differential fold changes in microarrays [83], various computational platforms using data-driven approaches (based on publicly available miR-disease databases) with network-based or machine learning algorithms to find novel miR-disease associations have been recently developed and validated [82,84,85,86,87,88,89,90,91,92].…”
Section: Discussionmentioning
confidence: 99%